If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -4x = 3x + -5 Reorder the terms: 2 + -4x = -5 + 3x Solving 2 + -4x = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + -4x + -3x = -5 + 3x + -3x Combine like terms: -4x + -3x = -7x 2 + -7x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + -7x = -5 + 0 2 + -7x = -5 Add '-2' to each side of the equation. 2 + -2 + -7x = -5 + -2 Combine like terms: 2 + -2 = 0 0 + -7x = -5 + -2 -7x = -5 + -2 Combine like terms: -5 + -2 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| e(2x+1)+7e(x)-15=0 | | 7x=31412+312 | | 36t^2+128t^3=9 | | -36t^2+128t^3=9 | | 5+3=x-3x-2x | | -72*t^2+256*t^3=18 | | x^10=1.55 | | x^10=15 | | 140x+x=180 | | -4x^3=-4x | | -2+a-b+1=0 | | 1+a+2b+4=0 | | x+4*3-4=65 | | (x-9)(x-12)=0 | | a=bx+cx^3 | | 7x-2y+4=o | | 2x-8x+13=26-x+14 | | 4-4x=4x+4 | | 3a+3b-2ab=0 | | 16-3x=11-21x | | 8-6x=9+x | | 13+7x=6-7x | | 8(3x-8x)(4x+9)=0 | | 14x-9=5x | | 17x-3=3x+11 | | 14x-9x=5x | | 29x=9+2x | | 9m-12=160 | | 15v=-8v | | x^3+8x^2+17x-4=0 | | lnx-ln(x-6)=3 | | lnx-ln(x+6)=3 |